(untitled) (Orfeu, 2022)
This study aims to promote and present how Music Education is formed in Brazil from the perspective of the scientific life trajectories of six outstanding researchers. The methodology used refers to research of a qualitative nature; documentary research; the digital curriculum as a source for data collection; the Biogram as a theoretical-methodological framework; and for the results, the interpretive paradigm of hermeneutics to arrive at the valuation of the collected data. The results demonstrate that the paths followed by these six researchers, despite being unique, converge towards the same end: consolidation and constant advances in their field of expertise. This can be confirmed watching at the various events in their trajectories. Thus, the trajectories of these researchers are a representation of an area of research and current professional. They are also collaborative for others who wish to follow the path of research and teaching. It is concluded that when considering uniqueness in the midst of plurality, it is possible to understand this area through the scientific-life trajectories of researchers. Giving visibility to the scientific-life trajectories in the area is to show, through this perspective, one of the various stories that composes the Music Education in Brazil.